Silicon smackdown. (Economist, 2025)
The article reports on the rivalry between chipmaker Nvidia and technology company Google in the development of artificial intelligence (AI) chips with Google's launch of Gemini 3 AI model, which was trained on Google chips called tensor-processing units (TPU). It refers to CUDA, the software platform that helps programmers make use of the Nvidia's graphics processing units, and the limitation of Google's willingness to sell its TPUs as the advantages of Nvidia.